An in vitro study of the impact of lead on dedifferentiation of mouse vascular smooth muscle cells - HONG Jiaying; LIU Suhui; LIANG Wenxi; NONG Qiying; HUANG Yongshun (Shanghai yufang yixue, 2025)
ObjectiveTo explore the role of lead exposure in the phenotypic transformation of vascular smooth muscle cells (VSMC), and to provide new insights for the mechanism of lead impact on vascular lesions.MethodsMouse aortic smooth muscle cells (MOVAS) were divided into a control group (0 μmol·L-1), low concentration lead groups (0.1, 1, 5, and 10 μmol·L-1), and high concentration lead groups (15, 25, and 50 μmol·L-1). MTT assays were used to assess the proliferation of the cells, and scratch assays were implicated to measure migration ability of the cells. Fluorescence quantitative PCR was employed to determine levels of mRNA expression for smooth muscle actin α (α⁃SMA), smooth muscle 22 alpha (SM22α), synthetic phenotype-related genes osteopontin (OPN), matrix metalloproteinase 9 (MMP9), and the transcription factor SOX9. Immunoblotting was used to determine levels of protein expression for α-SMA, OPN, and MMP9.ResultsProliferation of MOVAS was observed under the lead ions concentrations of 0‒50 µmol·L-1, with a significant increase of proliferation compared to the control group at the concentrations of 5‒50 µmol·L-1 (all P<0.05). The migration ability of cells gradually increased at the concentrations of 0‒10 µmol·L-1, with a significant increase at 5 (q=4.574, P=0.003) and 10 µmol·L-1 (q=10.570, P<0.001) compared to the control group. The 10 µmol·L-1 lead ions significantly reduced the levels of mRNA expression for vascular smooth muscle contractile phenotype genes α⁃SMA (q=7.426, P<0.001) and SM22α (q=4.766, P=0.001), while significantly increasing the levels of mRNA expression for OPN (q=11.330, P<0.001), MMP9 (q=7.842, P<0.001), and SOX9 (q=11.120, P<0.001) genes. Furthermore, the 10 µmol·L-1 lead ions significantly reduced the levels of protein expression for the vascular smooth muscle contractile phenotype marker α-SMA protein (q=2.897, P=0.049), while significantly increasing the levels of protein expression for the synthetic markers OPN (q=3.188, P=0.031) and MMP9 (q=3.292, P=0.026), compared to the control group.ConclusionTreatment with lead in vitro induced VSMC to differentiate from contractile phenotype to synthetic phenotype, indicating that a certain dose of lead exposure might be detrimental to the cardiovascular system.